1990
DOI: 10.1099/00221287-136-6-1145
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen autotrophy of Nocardia opaca strains is encoded by linear megaplasmids

Abstract: Several linear megaplasmids were detected in the facultatively lithoautotrophic Gram-positive bacterium Nocardia opaca The wild-type strain M R l l contains, in addition to the cccDNA plasmids pHG31-a and pHG31-b, the linear plasmids pHG201(270 kb), pHG202 (400 kb) and pHG203 (420 kb). The wild-type strain MR22 contains, in addition to the cccDNA plasmid pHG33, the linear plasmids pHG204 (180 kb), pHG205 (280 kb) and pHG206 (510 kb). After preparation of DNA from cells embedded in agarose, the linear plasmids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 13 publications
2
51
0
Order By: Relevance
“…The R. opacus wild-type strains MR11 and MR22 were each shown to contain three linear plasmids, pHG201 (270 kb), pHG202 (400 kb) and pHG203 (420 kb), as well as pHG204 (190 kb), pHG205 (280 kb) and pHG206 (500 kb), respectively (Kalkus et al, 1990). Two of these plasmids, pHG201 and pHG205, as well as pHG207, obtained from the transconjugant strain MR2253 (Kalkus et al, 1993), enable their hosts to grow chemolithoautotrophically on gaseous hydrogen and carbon dioxide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The R. opacus wild-type strains MR11 and MR22 were each shown to contain three linear plasmids, pHG201 (270 kb), pHG202 (400 kb) and pHG203 (420 kb), as well as pHG204 (190 kb), pHG205 (280 kb) and pHG206 (500 kb), respectively (Kalkus et al, 1990). Two of these plasmids, pHG201 and pHG205, as well as pHG207, obtained from the transconjugant strain MR2253 (Kalkus et al, 1993), enable their hosts to grow chemolithoautotrophically on gaseous hydrogen and carbon dioxide.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids of rhodococci, which, like their Streptomyces counterparts often possess linear topology, frequently encode catabolic genes, enabling their hosts either to grow with unusual carbon and energy sources such as CO 2 / hydrogen (Kalkus et al, 1990), (chloro)biphenyl (Kosono et al, 1997;Masai et al, 1997), and isopropylbenzene (Dabrock et al, 1994;Stecker et al, 2003) or to just convert such compounds as was shown for trichloroethene (Dabrock et al, 1994;Saeki et al, 1999). In addition, linear plasmids of rhodococci were shown to harbour genes for resistance to thallium (Kalkus et al, 1990) and arsenic (Dabrock et al, 1994;Stecker et al, 2003), as well as genes for phytopathogenicity (Maes et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear form is shared with various transposons (Grindley & Reed, 1985), adenoviruses (Tamanoi & Stillman, 1983) and the bacteriophage 429 from Bacillus subtilis (Escarmis & Salas,198 1). Among eubacteria, Streptomyces (Hayakawa et al, 1979;Hirochika & Sakaguchi, 1982;Hirochika et al, 1984;Kinashi et al, 1987;Kinashi & Shimaji-Murayama, 1991), Nocardia (Kalkus et al, 1990) and Borrelia (Barbour & Garon, 1987) seem to be the only genera having strains that harbour linear plasmids, whereas the great majority of plasmids described in other genera are found as covalently closed circular DNA molecules. Many Bacillus strains carry endogenous plasmids, several of which do not express useful or identifiable genetic markers (Lovett & Bramucci, 1975;Tanaka & Koshikawa, 1977;Tanaka & Sakaguchi, 1978;Uozumi et al, 1980;Gryczan, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…PFGE analysis using different pulse times showed that the relative migration of pSLV195, pSLV45 and pSLV325 remained constant relative to the linear lambda concatemers (data not shown). This indicates that the plasmids are linear rather than circular, since migration rates of circular plasmids change depending on the switch time used during electrophoresis (Kalkus et al, 1990;Kinashi & Shimaji-Murayama, 1991). …”
mentioning
confidence: 99%